The Influence of the Research-Based Learning Model on Improving Scientific Reasoning and Critical Thinking Skills of PGMI Students in Science Learning - Ratnawati Ratnawati; Susilawati Susilawati; Baryanto Baryanto; Aida Rahmi Nasution; Vira Ria Rinjiani (Journal of Primary Education (JPE), 2026)
This study aims to analyze the effect of the Research-Based Learning (RBL) model on improving scientific reasoning and critical thinking skills of PGMI students in the Science learning course. The study employed a quantitative approach with a quasi-experimental method and a pretest–posttest control group design. The research subjects consisted of two groups of PGMI students at IAIN Curup: the experimental group (n=30) that received learning using the RBL model and the control group (n=30) that received conventional learning. The research instruments were tests of scientific reasoning and critical thinking skills administered before (pretest) and after (posttest) the treatment. Data analysis used paired samples t-test and independent samples t-test. The results showed that: (1) there was a significant improvement in scientific reasoning skills of students in the RBL group from a pretest mean of 59.67 to 84.70 at posttest (p < 0.05); (2) there was a significant improvement in critical thinking skills from a mean of 57.83 to 69.33 (p < 0.05); and (3) there was a significant difference between the RBL group and the conventional group on both skills, with the RBL group obtaining higher scores (p < 0.05). These findings prove that the RBL model is effective in developing higher-order thinking skills of prospective madrasah ibtidaiyah teacher students. The implications of this study emphasize the importance of implementing RBL as an innovative learning alternative in higher education, particularly in teacher education programs, to prepare students for the demands of 21st-century skills